Indispensable Ocean : Aligning Ocean Health and Human Well-Being - Blue Ribbon Panel (Global Partnership for Oceans, Washington, DC, 2014)
A healthy ocean is fundamental to human wellbeing and an indispensable part of the Earth's life-support system, which sustains the species and the ecosystems upon which we depend. The ocean regulates our climate and, as part of the hydrological cycle, drives weather patterns that determine rainfall, droughts, and floods. The ocean has also reduced the impact of human-induced climate change by absorbing 25 percent of the carbon dioxide released by human activities and over 90 percent of the extra heat trapped by rising concentrations of atmospheric greenhouse gases. The ocean also provides food and sustains livelihoods. The size and growth of the human population is putting unprecedented pressure on natural resources, both on land and in the sea. The ocean may play an increasing role in supplying those resources and will, in this regard, play a critical role in global efforts to reduce poverty and improve livelihoods. Comprehensive global estimates of the economic activity associated with the ocean have only recently been attempted and a published consensus estimate has not yet emerged. The global economic benefits derived from the ocean's goods and services are, however, undeniably important, especially for coastal states and island nations. The ocean generates hundreds of millions of jobs in biotechnology, energy, fishing, shipping, tourism, and other sectors. Most current economic assessments do not yet fully account for the innumerable non-market ecosystem services that can deeply influence well-being, traditions, cultures, faith, and recreation and enjoyment for many millions of people.